Brassinosteroids: Alleviation of Water Stress in Certain Enzymes of Sorghum Seedlings - Seeta Ram Rao2, B. Vidya Vardhini1*, E. Sujatha1; S. (Journal of Phytology, 2011)
The effect of 28-homobrassinolide and 24-epibrassinolide on the activities of four oxidizing enzymes (superoxide dismutase, glutathione reductase, IAA oxidase and polyphenol oxidase) and two hydrolyzing enzymes (protease and ribonuclease) in the seedlings of four varieties of sorghum viz., CSH-15R, CSH-14, and ICSV-745 (susceptible to water stress) and M-35-1 (resistant to water stress) under PEG – imposed water stress was studied. Supplementation of both the brassinosteroids resulted in enhanced superoxide dismutase and glutathione reductase but lowered IAA oxidase, polyphenol oxidase, protease and ribonuclease activities indicating the alleviating ability of brassinosteroids on water stress in the drought sensitive as well as tolerant varieties of sorghum seedlings.